The Influence of Organizational Commitment, Fraud Seriousness Level, Personal Cost, and Professional Commitment on Whistle-blowing Intentions - Rahmanesya, Audria; Oktarina, Dian (FAKULTAS EKONOMI UNIVERSITAS MAARIF HASYIM LATIF, 2023)
Whistleblowing is an action taken by one or more people to uncover fraudulent behavior, both companies and individuals who commit fraud against other parties. This study examines the effect of organizational commitment, seriousness level of fraud, personal costs, and professional commitment on whistleblowing intentions. The research method used in this study is quantitative, with primary data obtained from distributing questionnaires. The population in this study are employees at commercial banks in the city of Surabaya. Sampling in this study using a purposive sampling method. The data in this study were processed using Partial Least Square Structural Equation Modelling (PLS-SEM) with SmartPLS 3.0 software. The results of this study state that organizational commitment has a positive effect on whistleblowing intentions. The seriousness level of fraud has a positive effect on whistleblowing intention. Personal costs do not affect whistleblowing intentions. Professional commitment does not affect whistleblowing intentions.